Wahdah Islamiyah And the Shift In Religious Education Affiliations Among Urban Muslim Communities In South Sulawesi And Gorontalo - Zaenuri, Ahmad; Podungge, Mariaty; Pakaya, Nurul Aini; Muchimah, Muchimah; Wahid, Abdul (JURNAL PENELITIAN, 2024)
The neo-Salafi movement Wahdah Islamiyah plays a significant role in shaping the religious identity of the urban Muslim middle class in South Sulawesi and Gorontalo. This research aims to review how Wahdah Islamiyah influences urban Muslim communities, leading to a high interest in religious studies and community education organized by this religious organization. The research method used is field research. This method was chosen because the researcher intends to gain clarity on a local and current event under study. This research concludes that Wahdah Islamiyah successfully manages its organization (framing) as a social movement to enhance its appeal to the public. Wahdah Islamiyah bridges or mediates the views between conservative-traditionalist Salafis and a more modern, open organizational management concept similar to Muhammadiyah. Wahdah Islamiyah adopts an organizational development concept through modern education by establishing Islamic schools, universities, social care institutions, and philanthropic organizations. The success of Wahdah Islamiyah’s framing gives the impression of an Islamic organization relatively open to modernity, yet still rooted in puritanical Islamic values like the Salafis, especially regarding fundamental religious issues such as aqidah (creed) and sharia (Islamic law). This religious model has proven to attract the Muslim middle class in South Sulawesi and Gorontalo.